Cardiac changes with subclinical hypothyroidism in obese women - Barış Kılıçaslan; Mustafa Kürşat Tigen; Ahmet Selami Tekin; Hilmi Çiftçi (KARE Publishing, 2013)
Objectives: Obesity has been linked to a spectrum of minor cardiovascular changes. The aim of this study was to determine the effect of obesity on cardiac functions and its relations with subclinical hypothyroidism in healthy women. Study design: Eighty-eight consecutive 'healthy' females (mean age: 31.2+-6.6 years) were included in the study. Thyroid function tests and echocardiography studies were performed in all patients. Height, weight, and waist and hip circumference were also measured. A body mass index (BMI) above 30 kg/m2 was considered obese. Results: Left ventricular mass (LVM) was higher in obese subjects (p<0.001). Doppler-derived indices of LV diastolic filling showed clear abnormalities of myocardial relaxation in obese subjects with higher E/e' (p=0.001) and larger left atrial volume (LAV) (p<0.001). LV myocardial performance index was also significantly higher in obese subjects (p=0.033). Thyroid-stimulating hormone (TSH) levels were significantly higher in obese subjects (p=0.011) and were positively correlated with BMI, waist circumference, LAV, and LVM. The prevalence of abnormal systolic and diastolic functions showed stepwise increases with higher TSH levels in obese subjects. Multiple regression analysis was used to evaluate the association of E/e' with anthromorphometric and biochemical parameters, and waist circumference was found to be the strongest independent variable correlated with the E/e' ratio. Conclusion: Cardiac structural and functional deteriorations may be related with subclinical hypothyroidism in obese subjects.